Meningkatkan Self Regulated Learning pada Siswa Melalui Strategi Belajar Berdasar Regulasi Diri - Dinda Permatasari Harahap (Journal on Education, 2023)
Self-regulated learning is a strategy carried out by students to regulate themselves and achieve optimal learning outcomes. This research aims to improve students' self-regulated learning through learning strategies based on self-regulation. The subject in this study was a 17-year-old high school student. This study used a single-subject experimental research design with a one-group pretest-posttest design. The treatment method given to the subject is based on learning strategies based on self-regulation, consisting of: 1) self-evaluation; 2) goal setting and strategic planning; 3) putting plans into action; and 4) monitoring outcomes. The results showed that there was an increase in the subject's self-regulated learning scale scores from low to moderate levels. Changes can also be seen from an increase in the duration of study hours and in the value of the subject's report card.